2022
DOI: 10.5267/j.ijdns.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of satisfaction and loyalty of e-banking users during the COVID-19 pandemic

Abstract: This research aims to analyze factors affecting e-banking user satisfaction and e-banking user loyalty during Covid-19 pandemic with e-banking service quality that consists of reliability, privacy and security, design on application or website, and customer service and assistance as the independent variables, while the dependent variables in this study are e-banking user satisfaction and e-banking user loyalty. This research was viewed based on an e-banking user perspective. This research used nonprobability s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 1 publication
3
15
0
Order By: Relevance
“…The results of this hypothesis are in line with the results of research conducted by (Manju, 2020), (Khatoon et al, 2020), and (Indrasari et al, 2022), which explained that a person's satisfaction depends on trust in the security of customer privacy itself and security is also the main indicator in customer satisfaction.…”
Section: The Effect Of Security On Customer Satisfactionsupporting
confidence: 88%
“…The results of this hypothesis are in line with the results of research conducted by (Manju, 2020), (Khatoon et al, 2020), and (Indrasari et al, 2022), which explained that a person's satisfaction depends on trust in the security of customer privacy itself and security is also the main indicator in customer satisfaction.…”
Section: The Effect Of Security On Customer Satisfactionsupporting
confidence: 88%
“…Supriyanto et al [ 37 ] found that better quality of online services results in delighted customers, which ultimately leads to increased loyalty of customers in online banking. Indrasari et al [ 17 ] researched the determinants of user satisfaction and user loyalty in online banking during Covid-19. They found service quality, reliability, application, and website design as significant determinants of user online satisfaction and loyalty.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Blockchain and smart contracts can be an effective solution to deal with the problems of counterfeiting, data security and privacy, operating costs, and bureaucratic barriers in the circular economy (Christidis, 2016;Saberi et al, 2019;Centobelli et al, 2022). There is an increase in customer confidence in each financial transaction to track product ownership (Jain et al, 2020;Indrasari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%